Ayn Rand's normative ethics the virtuous egoist - Smith, Tara 1961- (Cambridge University Press, 2006)
Ayn Rand is well known for advocating egoism, but the substance of that instruction is rarely understood. Far from representing the rejection of morality, selfishness, in Rand's view, actually demands the practice of a systematic code of ethics. This book explains the fundamental virtues that Rand considers vital for a person to achieve his objective well-being: rationality, honesty, independence, justice, integrity, productiveness, and pride. Tracing Rand's account of the harmony of human beings' rational interests, Smith examines what each of these virtues consists of, why it is a virtue, and what it demands of a person in practice. Along the way she addresses the status of several conventional virtues within Rand's theory, considering traits such as kindness, charity, generosity, temperance, courage, forgiveness, and humility. Ayn Rand's Normative Ethics thus offers an in-depth exploration of several specific virtues and an illuminating integration of these with the broader theory of egoism